Avaliação da analgesia pós-operatória da infusão contínua de Tiletamina/zolazepam em fêmeas caninas anestesiadas com isofluorano e submetidas à ovariohisterectomia - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The aim of the study was to evaluated postoperative the analgesia in dogs undergoing ovariohysterectomy, anesthetized with isoflurane, and continuous infusion of tiletamina-zolazepam. The animals were divided into two groups (n = 10): control group (CG) and tiletamina-zolazepam group (GTZ). MPA was performed with acepromazine (0.05 mg / kg) and meperidine (5 mg / kg) IM. Anesthesia induced with propofol (4 mg / kg) and was maintained with isoflurane (1.9% V), using controlled ventilation in all animals. After 10 minutes, the animals received GTZ bolus of 0.6 mg / kg tiletamine / zolazepam followed by continuous infusion at the rate of 0.06 mg / kg / min of the same drugs IV. The animals of the CG received bolus and continuous infusion of NaCl 0.9% in volume, rate and equal to the calculated routes for animals GTZ. The solutions were administered by infusion pump for 60 minutes. The surgical procedure was performed by the same surgical team. After extubation of animals and measurement of this time in both groups, the first assessment of analgesia was achieved and, thereafter, every 30 minutes for 4 hours (M0, M30, M60, M90, M120, M150, M180, M210, M240), drawing on the pain scale at the University of Melbourne, always performed by the same examiner who was unaware of the treatment administered. The analgesic rescue was performed with 4 mg / kg of tramadol in animals which received a score less than 12. Scores were statistically analyzed using the Mann-Whitney test. The need for rescue analgesia was assessed by survival Kaplan-Meier. In all analyzes, the significance level was 5%. To review the anesthetic recovery, the scale of recovery proposed by Pinho (2000) for determining the scores, which exemplifies values 1-5 listed in the classification score was used. Pain scores, expressed as median and maximum-minimum values: were significantly lower in the GTZ in T30 (7.5, 2:08), T90 (19, 5:09) and T150 (18.5, 6 and 10). The rescue analgesic was required in 70% of animals in any of the GC and GTZ. Analyzing the results, we can conclude that the use of the combination of tiletamina-zolazepam intraoperatively provided satisfactory analgesia in the immediate postoperative period, reducing the analgesic requirement.
Evaluation of postoperative analgesia of continuous infusion of Tiletamine / zolazepam in canine females anesthetized with isofluorane and submitted to ovariohysterectomy
Keywords: Analgesia; Tiletamina; Zolazepam; Ovariohisterectomia; Tiletamine; Zolazepam; Ovariohysterectomy